Protection of the Rights of the Elderly – Selected Administrative Law Issues - Augustyniak, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of this article is the analysis of selected instruments for the protection of the rights of seniors in terms of social policy and an attempt to assess the current senior policy in this respect. It concludes with de lege ferenda conclusions concerning the examined issues. The paper uses a dogmatic method.